Four Year Full State Funding, 1977 #1 - Missouri Southern State University (1977)
Leon Billingsly and Governor Christopher S. Bond standing next to the American Flag, in celebration of MSSU (MSSC at the time) becoming a fully state supported school; (left to right): Leon Billingsly, Gov. Bond.